DMITRY IVANOVICH SHIRSHOV – DOCTOR, SCIENTIST, INNOVATOR (on the 150th anniversary of the birth) - V. F. Bezhenar; E. F. Kira; A. S. Turlak; B. N. Novikov; K. E. Kira (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
IIn 2018, the 150th anniversary of Dmitrii I. Shirshov was celebrated. The article is devoted to Shirshov’s biography and describes his research pathway, the main achievements in obstetrics, gynecology and urogynecology. In addition, the article tells about the characteristic of his clinical and teaching activities.